Compañía de Teatro Independiente El Rostro: 38 años haciendo teatro desde Concepción - Sanhueza, María Teresa (Latin American Theatre Review, 2018)
Concepción is a Chilean city rich in history and culture, home to the legendary Teatro de la Universidad de Concepción (TUC), which was the most active regional university theater during the 1950’s and 1960’s. Three young, idealistic actors named Gustavo Sáez, XimenaRamírez, and Julio Muñoz founded the independent theatre company El Rostro in Concepción in 1978. This article traces the historiography of El Rostro during forty years of uninterrupted work in both dictatorship and democracy. During the Pinochet years, when most companies stopped their artistic endeavors due to censorship and political persecution, El Rostro was the only collective that managed to adapt, change, and survive while raising political and social consciousness. Risking their lives, they staged plays by Juan Radrigán (Las brutas, Testimonios de la muerte de Sabina, 1982), and Isadora Aguirre (Retablo de Yumbel, 1986). El Rostro’s history is a testament to the group’s commitment to its artistic mission and to the city. Today, theatre continues to flourish in Concepción and El Rostro remains in operation, revitalizing the stage with all kinds of productions, especially plays that educate the new generations through a strong repertoire of theatre for children.